Dissecting large and complex genomes: flow sorting and BAC cloning of individual chromosomes from bread wheat - Safár, Jan; Bartos, Jan; Janda, Jaroslav; Bellec, Arnaud; Kubaláková, Marie; Valárik, Miroslav; Pateyron, Stéphanie; Weiserová, Jitka; Tusková, Radka; Cíhalíková, Jarmila; Vrána, Jan; Simková, Hana; et al. (The Plant journal, 2004)
The analysis of the complex genome of common wheat (Triticum aestivum, 2n = 6x = 42, genome formula AABBDD) is hampered by its large size ( approximately 17 000 Mbp) and allohexaploid nature. In order to simplify its analysis, we developed a generic strategy for dissecting such large and complex genomes into individual chromosomes. Chromosome 3B was successfully sorted by flow cytometry and cloned into a bacterial artificial chromosome (BAC), using only 1.8 million chromosomes and an adapted protocol developed for this purpose. The BAC library (designated as TA-3B) consists of 67 968 clones with an average insert size of 103 kb. It represents 6.2 equivalents of chromosome 3B with 100% coverage and 90% specificity as confirmed by genetic markers. This method was validated using other chromosomes and its broad application and usefulness in facilitating wheat genome analysis were demonstrated by target characterization of the chromosome 3B structure through cytogenetic mapping. This report on the successful cloning of flow-sorted chromosomes into BACs marks the integration of flow cytogenetics and genomics and represents a great leap forward in genetics and genomic analysis.
Keywords: Chromosomes, Plant; In Situ Hybridization, Fluorescence; klonování DNA; pšenice; Genome, Plant; rostlinné geny; Genes, Plant; Flow Cytometry; hybridizace in situ fluorescenční; Chromosome Mapping; Triticum; průtoková cytometrie; Chromosomes, Artificial, Bacterial; mapování chromozomů; chromozomy rostlin; Cloning, Molecular; genom rostlinný; umělé bakteriální chromozomy; genová knihovna; Gene Library